Reshaping of Bilateral Gait Coordination in Hemiparetic Stroke Patients After Early Robotic Intervention - Puentes, Sandra; Kadone, Hideki; Watanabe, Hiroki; Ueno, Tomoyuki; Yamazaki, Masashi; Sankai, Yoshiyuki; Marushima, Aiki; Suzuki, Kenji (Frontiers in Neuroscience, 2018)
Hemiparetic gait is a common condition after stroke which alters importantly the quality of life of stroke survivors. In recent years, several robotic interventions have been developed to support and enhance rehabilitation strategies for such population. The Hybrid Assistive Limb® (HAL) robot suit is a unique device able to collect in real time bioelectric signals from the patient to support and enhance voluntary gait. HAL has been used before in early stages of stroke showing gait improvement after the intervention. However, evaluation of the coordination of gait has not been done yet. Coordination is a key factor for an adequate gait performance; consequently, its changes may be closely related to gait recovery. In this study, we used planar covariation to evaluate coordination changes in hemiparetic stroke patients after early HAL intervention. Before starting, impaired intersegmental coordination for the paretic and non-paretic side was evident. HAL intervention was able to induce recovery of the covariation loop shape and deviation from the covariation plane improving intersegmental coordination. Also, there was a tendency of recovery for movement range evidenced by comparison of peak elevation angles of each limb segment of the patients before and after HAL intervention, and also when compared to healthy volunteers. Our results suggest that early HAL intervention contributed to the improvement of gait coordination in hemiparetic stroke patients by reinforcing central pattern generators and therefore reshaping their gait pattern. Trial registration: UMIN000022410 2016/05/23.